Análisis contable de la implementación de la NIIF 9 sección 11 cuentas por cobrar en empresas PYMES (2020)
The article presented is intented to detail the way in wich SMEs companies should apply IFRS 9 – section 11 standard for the management of the accounts receivable ítem, since this account is relevant for organizations. Since it allows them to make order decisions financial; Methodologically, it is a review article, since the bibliographic exploration of the investigative tradition seeks to explain how IFRS 9 in its section 11 should be applied for the accounting treatment of the referred item.